Impacto do padrão geométrico ventricular na remodelação cardíaca após o infarto do miocárdio - Farah, Elaine [UNESP] (2013)
BACKGROUND: The relevance of left ventricular (LV) geometric pattern after myocardial infarction is not known. OBJECTIVES: To analyze the presence of different LV geometric patterns and teir impact as a predictor of remodeling in patients with myocardial infarction. METHODS: Patients with anterior acute myocardial infarction (n = 80) were divided according to the geometric pattern: normal (normal left ventricular mass index [LVMI] and normal relative wall thickness [RWT]), concentric remodeling (normal LVMI and increased RWT), concentric hypertrophy (increased LVMI and RWT) and eccentric hypertrophy (increased LVMI and normal RWT). After six months, echocardiographic assessment was repeated. RESULTS: Four patients died. Of the survivors, 41 showed remodeling (R +), whereas 39 did not (R-). Considering the geometric pattern, the cases were distributed as follows: 24 patients with normal pattern, 13 with concentric remodeling, 29 with concentric hypertrophy and 14 with eccentric hypertrophy. Patients who showed remodeling had larger infarction sizes analyzed by peak CPK (R + = 4,610 (1,688-7,970), R- = 1,442 (775-4247), p <0.001) and CK-MB (R + = 441 (246 - 666), R- = 183 (101-465), p <0.001), trend towards higher prevalence of concentric remodeling (R+ = 10, R- = 3, p = 0.08) and lower prevalence of eccentric hypertrophy (R + = 2 R- = 12, p = 0.006). In the multivariate regression analysis, infarction size was a predictor (OR = 1.01, p = 0.020) and eccentric hypertrophy was a protective factor (OR = 0.189, p = 0.046) of ventricular remodeling after coronary occlusion. CONCLUSION: The LV geometric pattern of can have an impact on the remodeling process in patients with myocardial infarction.